2017
DOI: 10.4253/wjge.v9.i1.19
|View full text |Cite
|
Sign up to set email alerts
|

Gastric antral webs in adults: A case series characterizing their clinical presentation and management in the modern endoscopic era

Abstract: AIMTo investigate the current management of gastric antral webs (GAWs) among adults and identify optimal endoscopic and/or surgical management for these patients.METHODSWe reviewed our endoscopy database seeking to identify patients in whom a GAW was visualized among 24640 esophagogastroduodenoscopies (EGD) over a seven-year period (2006-2013) at a single tertiary care center. The diagnosis of GAW was suspected during EGD if aperture size of the antrum did not vary with peristalsis or if a “double bulb” sign w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…[ 1 ] In recent years, several cases have shown that balloon dilatation combined with needle-knife incisions had low risk of perforation or significant bleeding and hence could also be a sufficient treatment modality. [ 5 7 8 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] In recent years, several cases have shown that balloon dilatation combined with needle-knife incisions had low risk of perforation or significant bleeding and hence could also be a sufficient treatment modality. [ 5 7 8 ]…”
Section: Discussionmentioning
confidence: 99%
“…GAW or antral mucosal diaphragm is a rare lesion reported in all ages, with an incidence of 0.14% in adults. 1,2 It consists of a layer of mucosa and submucosa lying perpendicular to the long axis of the stomach conjectured to occur during the healing of circumferential prepyloric ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…Though the absence of muscularis propria in GAW makes complications less likely, endotherapy should be performed cautiously. 2…”
mentioning
confidence: 99%